2017
DOI: 10.1159/000481918
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Methods for Estimation of Basal Metabolic Rate and Body Composition in Pediatric Patients with Osteogenesis Imperfecta

Abstract: Background/Aims: Osteogenesis Imperfecta (OI) is a bone disease characterized by bone fragility, deformities, and multiple fractures. The aim of this study was to compare the different methods of measuring the basal metabolic rate (BMR) and body composition (BC) in pediatric patients with OI. Methods: This cross-sectional study included 52 individuals with a median age of 9 (5.25–12.7) years. BMR was calculated by bioelectrical impedance analyses (BIA), predictive values according to age from the World Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“… have reported that BMI is not the best method for evaluating the body composition of these patients because BMI is a body height‐related measure and can be influenced by height loss as a result of leg deformities or scoliosis. Our previously published study showed a difference between the methods used to evaluate the body composition . Several studies have reported an association between OI and a higher BMI and being overweight .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“… have reported that BMI is not the best method for evaluating the body composition of these patients because BMI is a body height‐related measure and can be influenced by height loss as a result of leg deformities or scoliosis. Our previously published study showed a difference between the methods used to evaluate the body composition . Several studies have reported an association between OI and a higher BMI and being overweight .…”
Section: Discussionmentioning
confidence: 86%
“…and can be influenced by height loss as a result of leg deformities or scoliosis. Our previously published study showed a difference between the methods used to evaluate the body composition (14) . Several studies have reported an association between OI and a higher BMI and being overweight (7,9,19,20) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…/2018/ ТОМ 15/ № 3 рослости [2]. Типичными внескелетными проявлениями болезни являются невысокий рост, голубые склеры, несовершенный дентиногенез, прогрессирующее сниже-ние слуха, поражение соединительной ткани связочного аппарата [3].…”
Section: педиатрическая фармакологияunclassified
“…Dual-energy X-ray absorptiometry (DXA) uses ionising radiation from two sources that traverse the body and measure absorption by the bone, giving a clear evaluation of BMD which remains the gold standard [8] . This also allows a convenient means of assessing lean mass (LM), which consists of water, muscle, connective tissue and internal organs; and fat mass (FM), which is fat tissue; and is accessible to the majority of paediatric bone services [9,10] . Although used interchangeably and as a surrogate marker, LM is critically different to muscle mass.…”
Section: Introductionmentioning
confidence: 99%